(untitled) (SigMe, 2025)
Aging population is both a social issue and 21st century health challenge. During the last 50 years, The National Institute of Statistics and Censuses (INDEC) of Argentina has registered a steep decline in birth and mortality rates, with women living longer. This change in demographics allows the planning towards future healthier lifestyles and a more active aging, focusing on health promotion as key to securing people and community well-being, and health equity. In order to face this issue, an intervention project was designed to be developed in a nursing home. Its objective is to train older adults in self-care by making them adopt healthier habits, improving their autonomy, and empowering them so for their well-being and quality of life improvement. Self-care is closely related to individual, family, and community abilities to promote health, to prevent illnesses, to tackle diseases, and to deal with disabilities, leading to a progress. As it allows progess to be made in the right to health and reducing inequalities in the reduction of inequality. Health literacy allows for the patient to become empowered enough for their self-care (Málaga et al., 2019, p. 373). Health activities help prevent risk, delay dependency, reduce hospitalization, and keep older people active. That is why it is important to know which actions will be carried out: informative sessions, consultancy services, waiting room bulletin boards, and Cook a Healthy and Tasty Dish, Body on the Move, Active and the Use of Technology Everyday, Comunicating our Emotions, and Proposal of Activities Linking Institutions and Generations workshops.